KONFLIK KERJA-KELUARGA DAN KOMUNIKASI INTERPERSONAL DENGAN KEPUASAN PERNIKAHAN PADA KARYAWAN - Nuraeni Julianingsih, Nadya; Setiawan, Rony; Dian Iva Prestiana, Novita (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45 Bekasi, 2023)
Many couples find it difficult to balance work life and household life. In their work life, they often experience work conflicts, such asrisky work, insufficient work equipment, various work demands from superiors or colleagues, and so on. The purpose of this study was to determine the relationship and influence of workfamily conflict and interpersonal communication on marital satisfaction. The research method used is a quantitative approach, with interviews and psychological scale measurements. Subjects are employees as much as 255 respondents. The sampling technique is by purposive sampling with the criteria of employees who are married and have at least 1 child. The instrument uses the original scale or standard scale from the theory used. The results of the instrument test used the content validity test conducted by 4 raters, the construct validity test was tested on 70 respondents and the reliability test used Cornbach's alpha. Data analysis techniques using descriptive tests, assumption tests, and hypothesis testing. The results of the study are that there is a relationship between work- family conflict and marital satisfaction. There is a relationship between interpersonal communication and marital satisfaction. There is a significant influence between work-family conflict and interpersonal communication with marital satisfaction